(untitled) (Bangladesh Journal of Botany, 2021)
Investigation was carried out to ascertain the genetic architecture for heat tolerance and yield components from diallel crosses in maize (Zea mays L.). The combining ability in both the normal and heat stress conditions revealed highly significant mean squares due to general combining ability (GCA) and specific combining ability (SCA) in both the direct and reciprocal crosses for all the characters except for anthesis-silking interval in normal condition of the reciprocal crosses. Estimate of components of variance for 13 characters revealed higher SCA variance than that of GCA and reciprocal crosses for all the characters. CML 411 was good general combiner for grain yield in both the conditions, whereas, CML 306 and CML 307 were good general combiners in heat stress condition, and CML 164, CML 304 and CML 305 were average general combiners in normal condition. On the basis of high yield, high SCA and at least high GCA of seed parent, the CML 411*CML 305 and CML 411*CML 307 were identified as promising hybrids for normal and heat stress conditions, respectively. Bangladesh J. Bot. 50(3): 659-669, 2021 (September)